Renal Involvement in IgG4-Related Disease: From Sunlight to Twilight - Capecchi, Riccardo; Giannese, Domenico; Moriconi, Diego; Bonadio, Angelo G.; Pratesi, Federico; Croia, Cristina; Egidi, Maria F.; Puxeddu, Ilaria; Tavoni, Antonio G.; Migliorini, Paola (Frontiers in Medicine, 2021)
ABSTRACT IgG4-Related Disease (IgG4-RD) is a fibroinflammatory condition characterized by a typical histopathological pattern (dense lymphoplasmacytic infiltrate with prevalent IgG4+ plasma cells and storiform fibrosis), which may involve the kidney both directly (IgG4-related kidney disease, IgG4-RKD) or indirectly, as a consequence of post-renal ureteral obstruction due to retroperitoneal fibrosis (IgG4-RD RF). The most frequent presentation of IgG4-RKD is IgG4-related tubulointerstitial nephritis (TIN), but a glomerular disease can be present, in most of the cases a membranous nephropathy. Albeit steroid-responsive, in some cases renal manifestations may lead to progressive and permanent organ damage. In this review we describe four clinical cases representative of typical and less typical renal manifestations of IgG4-RD, emphasizing a potential, subclinical, early involvement of the kidney in the disease.